Characteristic comparison of human induced pluripotent stem cell-derived adult and fetal β-like cells: a differential gene expression analysis - Dany, F; Nikmah, U A; Mariya, S S; Panjaitan, N S D; Rinendyaputri, R; Sunarno (IOP conference series. Earth and environmental science, 2023)
Differentiating human induced pluripotent stem cells (hiPSCs) into β cells for type 1 diabetes (T1D) management is a crucial step. Functionality characterization of hiPSC-derived β cells in some cases, however, only considers morphology and proliferation aspect without examining their distinct molecular properties. Thus, we aimed to investigate the difference between hiPSC-derived adult and fetal β-like cells by differentially expressed gene (DEG) analysis. We retrieved one Gene Expression Omnibus (GEO) dataset with the ID GSE70901 comprising 16 samples and GEO2RAnalyze menu performed the analysis. Network clustering was conducted through the STRING version 12.0, Cytoscape version 3.10.0, and CytoCluster 1.0 plugin by considering overall centrality parameters. Enrichment analysis was performed in DAVID 2021 and updated Enrichr tools. Two main clusters were each related to ribosome and carbohydrate metabolism. Enrichment results showed that some molecular pathways might contrast hiPSC-derived adult from fetal β-like cells, notably ribosome ( p value <0.001). Cytoscape identified five significant subclusters with the densest one being ribosomal complex genes, such as RPS2, RPL5, and RPLP0 ( p value <0.001). This in silico analysis provides insights into genetic signatures with their potential role in pancreatic β cell maturation, which should be validated in more thorough studies.